PENGARUH INOVASI DIGITAL DAN KOMPETENSI KEWIRAUSAHAAN TERHADAP KEUNGGULAN BERSAING DAN DAMPAKNYA KE RESILIENSI BISNIS - Wahdi, Hilmy (2021)
This research aims to determine the impact of digital innovation and entrepreneurship on competitive advantage and its impact on business resilience by studying small, medium and micro-enterprises in the food and beverage sector during the Covid19 pandemic. The research method used in this study is a quantitative method. The survey was conducted by DepokCity among 150 small, medium and micro businesses in the food and beverage industry. The data analysis technique used in this study is structural equation modeling (SEM). The esults of this study found that (1) digital innovation affects competitive advantage, (2) digital innovation affects corporate resilience, (3) entrepreneurship affects competitive advantage, and (4) corporate literacy affects corporate resilience during the current pandemic. Therefore, competitive advantage and business resilience require digital innovation and entrepreneurial integrity